2022
DOI: 10.1177/18344909221138710
|View full text |Cite
|
Sign up to set email alerts
|

Finding meaning from the present and future: The mediating role of meaning in life between temporal focus and mental health

Abstract: Literature has shown that temporal focus (TF) is closely related to mental health, and both of them are associated with meaning in life (MIL). Nevertheless, few studies have investigated the functional role of MIL in the relationship between TF and mental health, especially in the context of COVID-19. The present study aims to explore the mediating role of MIL between different categories of TF (i.e., past, present, and future TF) and mental health. A two-wave longitudinal survey was conducted among 538 Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…A study by Dizon et al (2023) demonstrates the importance of hope as a viable resource in promoting individual well-being in the context of the COVID-19 pandemic. Zhou et al (2022) showed that past temporal focus negatively predicted meaning in life, whereas present and future temporal focus positively predicted meaning in life. In addition, meaning in life mediated the relationship between temporal focus and mental health indicators.…”
Section: The Covid-19 Pandemic and Individual Mental Healthmentioning
confidence: 96%
See 1 more Smart Citation
“…A study by Dizon et al (2023) demonstrates the importance of hope as a viable resource in promoting individual well-being in the context of the COVID-19 pandemic. Zhou et al (2022) showed that past temporal focus negatively predicted meaning in life, whereas present and future temporal focus positively predicted meaning in life. In addition, meaning in life mediated the relationship between temporal focus and mental health indicators.…”
Section: The Covid-19 Pandemic and Individual Mental Healthmentioning
confidence: 96%
“…Wei et al (2022) examined post-traumatic stress symptoms from the transactional theory of stress and coping (Lazarus & Folkman, 1987). The general conceptual model of time perspective (Zimbardo & Boyd, 1999) was used to explain the mediating role of life meaning between different categories of temporal focus and mental health (Zhou et al, 2022). Jin et al (2023), based primarily on the terror management theory (TMT; Greenberg et al, 1986), found that death anxiety is a significant positive predictor of overall mental health and meaningfulness of life.…”
Section: Theories Used In This Special Issuementioning
confidence: 99%
“…Using the type of social norm as the independent variable (working-together norms = 1, no working-together normative-information social norms = 0), perceived behavioral control and intentions towards pro-environmental donations as mediating variables, proenvironmental donations as the dependent variable, and gender and age as covariates, 5000 samples were extracted using the bootstrapping method to for 95% confidence interval (95% CI) estimations. To reduce multicollinearity [47], in reference to previous studies [48,49], all data have been mean-centralized, and the following results are presented as standardized coefficients. The predictive effect of the type of social norms on perceived behavioral control was significant, β = 0.20, SE = 0.09, p = 0.022, 95% CI = [0.03, 0.38].…”
Section: Chain Mediation Modelmentioning
confidence: 99%
“…Presence of meaning refers to a person's view of their life as meaningful, purposeful, and important (Steger et al, 2006). Previous research has shown that an increased connection to the future is beneficial for enhancing the level of presence of meaning, which promotes the psychological well-being of individuals (Zhou et al, 2022). Thus, future self-continuity may indirectly affect depression in college students through the presence of meaning.…”
Section: Mediating Role Of the Presence Of Meaningmentioning
confidence: 99%